Extensions 1→N→G→Q→1 with N=C3 and Q=He34S3

Direct product G=N×Q with N=C3 and Q=He34S3

Semidirect products G=N:Q with N=C3 and Q=He34S3
extensionφ:Q→Aut NdρLabelID
C3⋊(He34S3) = C3410C6φ: He34S3/C3×He3C2 ⊆ Aut C381C3:(He3:4S3)486,242

Non-split extensions G=N.Q with N=C3 and Q=He34S3
extensionφ:Q→Aut NdρLabelID
C3.1(He34S3) = C33⋊D9φ: He34S3/C3×He3C2 ⊆ Aut C381C3.1(He3:4S3)486,137
C3.2(He34S3) = He33D9φ: He34S3/C3×He3C2 ⊆ Aut C381C3.2(He3:4S3)486,142
C3.3(He34S3) = C344C6φ: He34S3/C3×He3C2 ⊆ Aut C327C3.3(He3:4S3)486,146
C3.4(He34S3) = C9⋊He32C2φ: He34S3/C3×He3C2 ⊆ Aut C381C3.4(He3:4S3)486,148
C3.5(He34S3) = (C32×C9)⋊C6φ: He34S3/C3×He3C2 ⊆ Aut C381C3.5(He3:4S3)486,151
C3.6(He34S3) = C345C6φ: He34S3/C3×He3C2 ⊆ Aut C327C3.6(He3:4S3)486,167
C3.7(He34S3) = C324D9⋊C3φ: He34S3/C3×He3C2 ⊆ Aut C381C3.7(He3:4S3)486,170
C3.8(He34S3) = He3⋊C33S3φ: He34S3/C3×He3C2 ⊆ Aut C381C3.8(He3:4S3)486,173
C3.9(He34S3) = C3≀C3.S3φ: He34S3/C3×He3C2 ⊆ Aut C3276+C3.9(He3:4S3)486,175
C3.10(He34S3) = C33⋊C18central extension (φ=1)54C3.10(He3:4S3)486,136
C3.11(He34S3) = C343S3central stem extension (φ=1)186C3.11(He3:4S3)486,145
C3.12(He34S3) = (C32×C9)⋊8S3central stem extension (φ=1)546C3.12(He3:4S3)486,150
C3.13(He34S3) = C345S3central stem extension (φ=1)186C3.13(He3:4S3)486,166
C3.14(He34S3) = He3.C3⋊S3central stem extension (φ=1)546C3.14(He3:4S3)486,169
C3.15(He34S3) = He3⋊C32S3central stem extension (φ=1)546C3.15(He3:4S3)486,172